(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
In the framework of a re-examination of Symbola, the volume dedicated by Gauthier to foreigners and justice, the author of this essay focuses his attention on chapter I, in particular on the figure and role of the proxenos (taking into account the main opinions subsequently expressed in literature), and on chapter V, in particular on the role of protection of the foreigner ensured by the grants of asylia. To clarify the scope of this privilege, it was deemed useful to compare the traditional way of understanding the sylai, i.e. the ‘saisies’ in Gauthier’s language, with the critique of this opinion carried out by B. Bravo in 1980. At the end of his analysis, the author holds the view that many of the research directions on these topics indicated by Gauthier, deserve to be taken into serious consideration by those who wish to continue the study of relations between citizens and foreigners in the Greek world.